A benchmarking and comparative analysis of emotional intelligence in student and qualified radiographers: an international study. Issue 4 (1st September 2015) - Mackay, Stuart James; White, Peter; McNulty, Jonathan P.; Lane, Steven; Lewis, Sarah Jayne
Abstract: Introduction: Emotional intelligence (EI) has been identified as an important trait for healthcare students and healthcare professionals alike and is a predictor of improved work performance and patient satisfaction. In this paper, we benchmark an international cohort of radiography students and compare their scores to those of known qualified practitioner and normative data. Methods: EI scores were at commencement from radiography degree programmes at four universities in Australia, Hong Kong, Republic of Ireland and the United Kingdom using the short form of the trait EI questionnaire (TEIQue‐SF), which yields a Global score and four sub‐factors. In total 293 students chose to participate. Results: For the Australian combined Irish and UK groups, there were significant differences in Global EI and three of the four sub‐factors between students and qualified radiographers (Australia: students = 5.01, qualified = 5.27; P  ≤ 0.01) (Irish/UK students = 5.04, qualified = 5.28; P  ≤ 0.01). When compared to the UK normative data, there was a significant difference for Global EI between the UK students and the UK norm data set (students = 4.71, normative = 4.99; P  ≤ 0.01). Conclusion: This study provides benchmarking data for an international radiography student group. The clear differences of higher EI scores for qualified practicing radiographers when compared to student score opens discussion of the impact of academic and clinical practicum as a contributing factor in EI skills development. Abstract : This article compares the emotional intelligence (EI) of diagnostic and therapy student radiographers against qualified radiographers. It is an international study across four universities and looks at the impact of working and academic environments on the EI of radiographers.